Inflation Uncertainty, Output Growth Uncertainty and Macroeconomic Performance: Comparing Alternative Exchange Rate Regimes in Eastern Europe - Muhammad Khan; Mazen Kebewar; Nikolay Nenovsky (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In the late 90's, after severe financial and economic crisis, accompanied by inflation and exchange rate instability, Eastern Europe emerged into two groups of countries with radically contrasting monetary regimes (Currency Boards and Inflation targeting). The task of our study is to compare econometrically the performance of these two regimes in terms of the relationship between inflation, output growth, nominal and real uncertainties from 2000 till now. In other words, we test the hypothesis of non-neutrality of monetary and exchange rate regimes with respect to these connections. In a whole, the empirical results do not allow us to judge which monetary regime is more appropriate and reasonable to assume. EU enlargement is one of the possible explanations for the numbing of the differences and the lack of coherence between the two regimes in terms of inflation, growth and their uncertainties.
Keywords: C22; C51; C52; E0; 330; Inflation; Inflation uncertainty; Real uncertainty; Monetary regimes; Eastern Europe